Numerical simulation of the fracture process in ceramic FPD frameworks caused by oblique loading. (October 2015) - Kou, Wen; Qiao, Jiyan; Chen, Li; Ding, Yansheng; Sjögren, Göran
Abstract: Using a newly developed three-dimensional (3D) numerical modeling code, an analysis was performed of the fracture behavior in a three-unit ceramic-based fixed partial denture (FPD) framework subjected to oblique loading. All the materials in the study were treated heterogeneously; Weibull׳s distribution law was applied to the description of the heterogeneity. The Mohr–Coulomb failure criterion with tensile strength cut-off was utilized in judging whether the material was in an elastic or failed state. The simulated loading area was placed either on the buccal or the lingual cusp of a premolar-shaped pontic with the loading direction at 30°, 45°, 60°, 75° or 90° angles to the occlusal surface. The stress distribution, fracture initiation and propagation in the framework during the loading and fracture process were analyzed. This numerical simulation allowed the cause of the framework fracture to be identified as tensile stress failure. The decisive fracture was initiated in the gingival embrasure of the pontic, regardless of whether the buccal or lingual cusp of the pontic was loaded. The stress distribution and fracture propagation process of the framework could be followed step by step from beginning to end. The bearing capacity and the rigidity of the framework vary with the loading position and direction. The framework loaded with 90° towards the occlusal surface has the highest bearing capacity and the greatest rigidity. The framework loaded with 30° towards the occlusal surface has the least rigidity indicating that oblique loading has a major impact on the fracture of ceramic frameworks. Graphical abstract: Highlights: Effects of oblique loading on stress distribution could be studied. The fracture of the framework started in the occlusal area due to compression. The cause of fracture in the framework was mainly tensile stress. Stress distribution and fracture propagation could be followed step by step. Loading position and direction affected the load capacity and rigidity.